Battling and managing disease - 4 0 16; Rogers, Kara.; 5 (New York : Britannica Educational Publishing in association with Rosen Educational Services, 2011)
An exploration of the public health and disease that provides information on the history of public health, international organizations, financial and legal aspects of health care, noncommunicable and communicable diseases, research, treatments, and more.
Includes bibliographical references (p. [196]-199) and index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; history. -- Public health;Medicine, Popular.;Delivery of Health Care.;Disease;Cross-Cultural Comparison.;Developed Countries.;Developing Countries.;Socioeconomic Factors.;Public health.;Popular medicine. -- Popular works; 20; 2